Improving D‐2‐hydroxyglutarate MR spectroscopic imaging in mutant isocitrate dehydrogenase glioma patients with multiplexed RF‐receive/B0‐shim array coils at 3 T. (5th October 2021) - Strasser, Bernhard; Arango, Nicolas S.; Stockmann, Jason P.; Gagoski, Borjan; Thapa, Bijaya; Li, Xianqi; Bogner, Wolfgang; Moser, Philipp; Small, Julia; Cahill, Daniel P.; Batchelor, Tracy T.; Dietrich, Jorg; et al.
Abstract : MR spectroscopic imaging (MRSI) noninvasively maps the metabolism of human brains. In particular, the imaging of D‐2‐hydroxyglutarate (2HG) produced by glioma isocitrate dehydrogenase (IDH) mutations has become a key application in neuro‐oncology. However, the performance of full field‐of‐view MRSI is limited by B0 spatial nonuniformity and lipid artifacts from tissues surrounding the brain. Array coils that multiplex RF‐receive and B0 ‐shim electrical currents (AC/DC mixing) over the same conductive loops provide many degrees of freedom to improve B0 uniformity and reduce lipid artifacts. AC/DC coils are highly efficient due to compact design, requiring low shim currents (<2 A) that can be switched fast (0.5 ms) with high interscan reproducibility (10% coefficient of variation for repeat measurements). We measured four tumor patients and five volunteers at 3 T and show that using AC/DC coils in addition to the vendor‐provided second‐order spherical harmonics shim provides 19% narrower spectral linewidth, 6% higher SNR, and 23% less lipid content for unrestricted field‐of‐view MRSI, compared with the vendor‐provided shim alone. We demonstrate that improvement in MRSI data quality led to 2HG maps with higher contrast‐to‐noise ratio for tumors that coincide better with the FLAIR‐enhancing lesions in mutant IDH glioma patients. Smaller Cramér–Rao lower bounds for 2HG quantification are obtained in tumors by AC/DC shim, corroborating with simulations that predicted improved accuracy and precision for narrower linewidths. AC/DC coils can be used synergistically with optimized acquisition schemes to improve metabolic imaging for precision oncology of glioma patients. Furthermore, this methodology has broad applicability to other neurological disorders and neuroscience. Abstract : 2HG imaging is a key application in neuro‐oncology for detecting the IDH status of tumors, but it is limited by B0 spatial nonuniformity and lipid artifacts. AC/DC coils mitigate these limitations and improve MRSI data quality, which leads to increased precision and accuracy of 2HG quantification in mutant IDH glioma patients.